(untitled) (Fiep Bulletin - online, 2012)
Studies from several well-Known authors in plastic area and others from linfology show an intense vascular and lymphatic injury after the abdominal dermolipectomy surgery. In consequence of the aggression, the organism develops an inflammatory process that leads to edema, and this edema is the extra cellular liquid expansion of the organism. For this reason, it is the vital importance for the surgery’s success that the extension of the edema to be kept in a minimum proportion. This work has the purpose of accomplishing a bibliography study about the manual lymphatic drainage, as well as its advantages and efficacy on patient’s application submitted to abdominal dermolipectomy surgery. Beyond working on the edema and hematoma after surgery, the lymphatic massage discharges an auxiliary role in the injuries. The acute trauma or chronic inflammation in the healing process depends entirely on the efficiency of the sanguine and lymphatic circulation.